2019
DOI: 10.9771/cmbio.v18i2.29698
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de vaginoses bacterianas em pacientes que realizaram bacterioscopia de secreção vaginal

Abstract: <strong>Introdução</strong>: a microbiota da região genital feminina pode sofrer alterações ocasionando patologias, como as vaginoses bacterianas (VB). A VB tem como principal sintoma o corrimento vaginal, de coloração branca ou acinzentada com odor desagradável. Devido as grandes complicações que essa doença ocasiona, como infertilidade, abortamentos e o aumento do risco de adquirir HIV, ela é considerada um grave problema de saúde pública. <strong>Objetivo</strong>: verificar a preval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 2 publications
0
6
0
3
Order By: Relevance
“…The normal vaginal microbiota is formed by several aerobic, anaerobic and facultative bacteria, being highlighted in the literature as an important protective factor against pathogens in the genital tract, and carries important reproductive function defense mechanisms, as it prevents multiplication of pathogenic microorganisms (Klebanoff and Coombs, 1991;Resende et al, 2019). Modifications in the vaginal microbiota can cause cervicovaginal infections accompanied by an abundant, homogeneous, grayish white, non-purulent vaginal discharge, with an extremely unpleasant odor, known as bacterial vaginoses (Gallo and Fabião, 2016).…”
Section: Agents Causing Genital Infections In Routine Cytological Tests: Frequency and Characteristics Of Papanicolaou Smears 1 Introductmentioning
confidence: 99%
See 1 more Smart Citation
“…The normal vaginal microbiota is formed by several aerobic, anaerobic and facultative bacteria, being highlighted in the literature as an important protective factor against pathogens in the genital tract, and carries important reproductive function defense mechanisms, as it prevents multiplication of pathogenic microorganisms (Klebanoff and Coombs, 1991;Resende et al, 2019). Modifications in the vaginal microbiota can cause cervicovaginal infections accompanied by an abundant, homogeneous, grayish white, non-purulent vaginal discharge, with an extremely unpleasant odor, known as bacterial vaginoses (Gallo and Fabião, 2016).…”
Section: Agents Causing Genital Infections In Routine Cytological Tests: Frequency and Characteristics Of Papanicolaou Smears 1 Introductmentioning
confidence: 99%
“…Some studies have demonstrated the importance of the Pap smear method for the diagnosis of vaginal infection causing agents (Aragão et al, 2019;Matos-Rocha, 2019;Xavier et al, 2019;Resende et al, 2019). Thus, the objective 3/6 Detection of infections including it's initial stages, and can also identify noncancerous conditions such as infection or inflammation.…”
Section: Agents Causing Genital Infections In Routine Cytological Tests: Frequency and Characteristics Of Papanicolaou Smears 1 Introductmentioning
confidence: 99%
“…Thus, this infection is considered the most prevalent curable STI in the world, showing a peak in the 30-39 age group, with a cosmopolitan distribution among women and men, and in all socioeconomic and racial groups (4) .Bacterial vaginosis (BV) is the most common cause of abnormal vaginal secretion in women of reproductive age (5) . In Brazil, its prevalence ranges from 18.4 to 36.0% (6)(7)(8) . Although it is not considered an STI, it shares risk factors with these infections, such as a higher frequency in sexually active women with multiple sexual partners (9) .…”
mentioning
confidence: 99%
“…Bacterial vaginosis (BV) is the most common cause of abnormal vaginal secretion in women of reproductive age (5) . In Brazil, its prevalence ranges from 18.4 to 36.0% (6)(7)(8) . Although it is not considered an STI, it shares risk factors with these infections, such as a higher frequency in sexually active women with multiple sexual partners (9) .…”
mentioning
confidence: 99%
“…The vaginal microbiota is formed by several aerobic, anaerobic and facultative bacteria, being considered one of the most important defense mechanisms of the reproductive function, as it prevents the growth of pathogenic microorganisms (Resende et al, 2019). The bacterial microbiota in the vagina of a healthy woman of reproductive age is dominated by lactobacilli (Wójkowska-Mach et al, 2021).…”
mentioning
confidence: 99%